Visual revisions: Sweet Charity Group’s 1980 – 1984 album covers/ Muhammad Asri Azuddin ... [et al.] - Azuddin, Muhammad Asri; Shafie, Norhaslinda; Azman, Mohammad Firdaus; Halili, Nur Akma; Sulaiman, Mohamad Zaidi; Che Saad, Muhamad Adam Hanif (Universiti Teknologi MARA, Perak, 2024)
An album can be evaluated using a variety of different approaches. Making record covers with artwork that is visually appealing and captivating is an approach that has shown to be incredibly effective. As a consequence of this, the purpose of this study is to analyze the influence that visual modifications have had on the album cover of Sweet Charity Group. During the course of this research, a comparative methodology was applied to investigate the album covers of five different albums: Pelarian (1980), Sejuta Wajah (1981), Penunggu (1982), Batu (1983), and Koleksi Sweet Charity (1984). An examination of record covers was carried out in order to ascertain the visual approach that architects and designers most frequently employ. Without a shadow of a doubt, the subfield of visual arts has seen substantial transformations, particularly with regard to the influence of visual components. Visual components will be used to evaluate and judge the outcomes of the chats as well as the results. Ultimately, the researchers came to the conclusion that photography, color, and typography are three essential elements that have the potential to impact the design of album covers.